Characteristics of Palestinian Economy and It’s Competitive Advantage of Porter’s Theory and Diamond Model - Barghouthi, Orobah Ali (International Journal of Marketing Research Innovation, 2017)
The study focused on the advancing the competitive advantage of Palestine. The Palestine Investment Fund as government body in enhancing competitive advantage of Palestinian economy, the study sought to answer the research aim.